1972
DOI: 10.1039/c39720000059
|View full text |Cite
|
Sign up to set email alerts
|

α-Cupriobenzylideneamines, a novel class of thermally stable organocopper compounds

Abstract: Insertion of isocyanides into the Cu-C bond of arylcopper ( I) compounds affords novel, thermally stable a-cupriobenzylideneamines.RECENTLY we reported the isolation and characterization of thermally, oxidatively, and hydrolytically stable arylcopper(1) compounds which contain, preferably in the ortho position, hetero-atom containing substituents (e.g. NMe,, OMe, CH,-NMe,, and CH,.OMe).l We have now found that these compounds readily react with isocyanides to afford a-cupriobenzylideneamines instead of organoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
2

Year Published

1975
1975
2004
2004

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 0 publications
3
49
0
2
Order By: Relevance
“…However, it is assumed that the main structural features for the compounds I-V (multicenter bonded aryl groups; tetranuclear Cu, cluster) are retained in solution. This view seems justified, (I) by the observation that both in the solid and in solution the compounds are tetranuclear and (ii) by the proof [ 20,211 for multicenter bonded aryl groups in the related R4CuzLiz and R,Ag,Li, compounds in solution. As follows from Table 2 and Fig.…”
Section: Mass Spectrometrymentioning
confidence: 98%
“…However, it is assumed that the main structural features for the compounds I-V (multicenter bonded aryl groups; tetranuclear Cu, cluster) are retained in solution. This view seems justified, (I) by the observation that both in the solid and in solution the compounds are tetranuclear and (ii) by the proof [ 20,211 for multicenter bonded aryl groups in the related R4CuzLiz and R,Ag,Li, compounds in solution. As follows from Table 2 and Fig.…”
Section: Mass Spectrometrymentioning
confidence: 98%
“…Although further study is necessary to disclose the reaction mechanism, the high diastereoselectivity observed in the 1,4-addition of arylcopper reagents is consistent with previous proposals. 2,6) Since it is assumed that the conjugate addition takes place via the s-cis conformation 6) of a,b-unsaturated tertiary amide 1, a diarylcopper reagent, which would be dimeric, 14) could attack preferentially from the C(3)-Re face of transition state A, affording 4 as shown in Fig. 1.…”
Section: )mentioning
confidence: 99%
“…Recently van Koten et al (6) have used the chiral labelling technique (10) to show that the Hg-N coordination is stable on the nmr time scale at -70°C in LHgX compounds (X = CI, OAc), but becomes labile at higher temperatures.…”
Section: Nuclear Magnetic Resonance Spectroscopymentioning
confidence: 99%